Biomass and nutrient accumulation by the spontaneous vegetation in organic coffee crops - Ricci, Marta dos Santos Freire; Costa, Janaina Ribeiro; Viana, Abraão José Silva; Risso, Ilzo Artur Moreira (Coffee Science - ISSN 1984-3909, 2010)
To evaluate biomass production and nutrient accumulation by the spontaneous vegetation in organic coffee crops and the phytosociology of these species, an experiment was set up at Fazendinha Agroecológica, in Seropédica, Rio de Janeiro state, in Brazil. The experiment consisted of three treatments, corresponding to systems of cultivation of conilon coffee (Coffea canephora Pierre ex A. Froehner) in association with the tree legumes Gliricidia sepium (Jacq.) Kunth ex Walp. and Erythrina variegata L. (treatments 1 and 2), and a full sun cultivation system (treatment 3), distributed in a random block design with six replicates. Although six hoeings were performed over the course of one year, the aerial biomass produced by the spontaneous vegetation and the N, P, K, Ca, Mg and micronutrient contents accumulated in it were measured in only five periods4, to estimate the amount of nutrients that could be recycled after decomposition. The phytosociology of the spontaneous vegetation was evaluated in October 2006 and June 2007. Based on the species found, richness, abundance, relative frequency of species and Shannon’s diversity index were determined. The most significant biomass production values were obtained between October and December 2006, the highest results being found in coffee grown with gliricidia. No differences regarding the N, K, and Ca contents in the biomass were observed between the different treatments; however, the highest P content was registered in coffee grown in the full sun system, while the highest Mg content was found in coffee grown with gliricidia. The diversity of plant species is small and no differences can be observed among the systems. The most frequent invasive plant species in the systems, in both periods evaluated, were Commelina diffusa Burm. f. and Paspalum conjugatum L.